Relationship between the abnormal diastolic vortex structure and impaired left ventricle filling in patients with hyperthyroidism. Issue 17 (April 2017) - Zhou, Bin-Yu; Xie, Ming-Xing; Wang, Jing; Wang, Xin-Fang; Lv, Qing; Liu, Man-Wei; Kong, Shuang-Shuang; Zhang, Ping-Yu; Liu, Jin-Feng
Abstract : Abstract: Intraventricular hydrodynamics plays an important role in evaluating cardiac function. Relationship between diastolic vortex and left ventricular (LV) filling is still rarely elucidated. The aim of this study was to evaluate the evolution of vortex during diastole in hyperthyroidism (HT) and explore the alteration of hydromechanics characteristics with sensitive indexes. Forty-three patients diagnosed with HT were classified into 2 groups according to whether myocardial damage existed: simple hyperthyroid group (HT1, n = 21) and thyrotoxic cardiomyopathy (HT2, n = 22). Twenty-seven age- and gender-matched healthy volunteers were enrolled as the control group. Offline vector flow mapping (VFM model) was used to analyze the LV diastolic blood flow patterns and fluid dynamics. Hemodynamic parameters, vortex area (A), circulation (C), and intraventricular pressure gradient (Δ P ), in different diastolic phases (early, mid, and late) were calculated and analyzed. HT2, with a lower E/A ratio and left ventricular ejection fraction (LVEF), had a larger left atrium diameter (LAD) compared with those of the control group and HT1 ( P  < .05). Compared with the control group, the vortex size and strength, intraventricular pressure gradient during early and mid-diastole were higher in HT1 and lower in HT2 ( P  < .05). And in late diastole, the vortex size and strength, intraventricular pressure gradient of HT2 became higher than those of the control group ( P  < .05). Good correlation could be found between CE and E/A ( P  < .05),  CM and ΔPM ( P  < .01),  CL and FT3 ( P  < .05). VFM is proven practical for detecting the relationship between the changes of left ventricular diastolic vortex and the abnormal left ventricular filling.